A Field-based Approach to Support Improved Diabetes Care in Rural States - Elizabeth A. Johnson, BSN, APRN; Wanda L. Webb, RN, MHA; Janet M. McDowall, RN, BSN; Linda L. Chasson, MSA; Carrie S. Oser, MPH; Joseph R. Grandpre, PhD, MPH; Madhavi I. Marasinghe; Marcene K. Butcher, RD, CDE; Erin M. O'Leary; Todd S. Harwell, MPH; Dorothy Gohdes, MD; Steven D. Helgerson, MD, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Diabetes care is a challenge in rural areas where primary care practices are faced with limited resources, few clinical information systems, and relative isolation from education programs and diabetes centers with multispecialty teams. This report describes an effective field-based approach to support improved care for patients with diabetes in primary care practices in rural states. Methods A collaborative effort between diabetes prevention and control programs in Montana and Wyoming and the University of North Dakota was established to provide support to rural primary care practices for improvement in diabetes care. Field teams from each state diabetes program approached primary care practices. After assessment and orientation of office staff, a computer-based registry was established in each practice. Baseline data were collected in 1997 in Montana and in 1998 in Wyoming; follow-up occurred on July 31, 2004. Health department staff provided ongoing technical support for implementing and evaluating quality-improvement interventions. Results Forty primary care practices, providing care to more than 7000 patients with diabetes, participated in this quality-improvement effort at follow-up. Of the 37 primary care practices participating in the quality-improvement program for 6 or more months at follow-up, there were significant improvements in Montana in rates of hemoglobin A1c testing, blood glucose control, low-density lipoprotein cholesterol testing, foot and dilated retinal examinations, and pneumococcal vaccinations, and there were significant improvements in pneumococcal vaccinations in Wyoming. Conclusion A field-based approach in which individual practices maintain and use their own registries for both clinical care and quality improvement with ongoing support is a sustainable and an effective strategy for improving diabetes care for rural populations.